Cardiometabolic risk among schoolchildren born at term and premature (Research, Society and Development, 2021)
Objective: To assess the occurrence of cardiometabolic risk (RCmet) in children aged 5 to 9 years old born premature compared to those born at term. Methodology: Cross-sectional study in which children enrolled in urban municipal schools were evaluated. They were divided into two groups: low income and middle income, considering that the economic status is one of the social determinants of health. The total sample was of 132 children, classified according to their gestational age at birth in a group of schoolchildren born at term (GST) and a group of schoolchildren born prematurely (GSP), and assessed for weight, height, waist circumference (WC), blood pressure (BP), capillary blood glucose (CBG), total cholesterol (TC) and triglycerides (TG). RCmet was also analyzed in both groups according to the WC in the >90th percentile and the >50th percentile, associated with at least two of the following criteria: TC ≥70 mg/dL; TG ≥85 mg/dL; CBG ≥126 mg/dL; Systolic/diastolic BP ≥P90 mmHg, and the WC and height ratio (WCHR). Results: Among the GST with WC >P90, 10% presented RCmet, while, for the WC >P50, 23.44% presented this risk. In GSP, there were no participants with WC above P90; in those with WC >P50, 22.22% had RCmet. Comparing the groups, there was no statistically significant difference. It was found that in 90.15% of the evaluations, there was an equivalent classification between the HR methods and the WC percentile. Conclusions: The occurrence of RCmet was evidenced in both groups, however, there was no influence of the age at birth on this risk.